Introduction to cities how place and space shape human experience - Chen, Xiangming 1955-; Orum, Anthony M.; Paulsen, Krista E. (Chichester, West Sussex, United Kingdom Wiley-Blackwell, 2013)
"A complete introduction to the history, evolution, and future of the modern city, this book covers a wide range of theory, including the significance of space and place, to provide a balanced account of why cities are an essential part of the global human experience. Covers a wide range of theoretical approaches to the city, from the historical to the cutting edge Emphasizes the important themes of space and place Offers a balanced account of cities and offers extensive coverage including urban inequality, environment and sustainability, and methods for studying the city Takes a global approach, with examples from Berlin and Chicago to Shanghai and Mumbai Includes a range of pedagogical features such as a substantial glossary of key terms, critical thinking questions, suggestions for further reading and a range of innovative textboxes which follow the themes of Exploring Further, Studying the City and Making the City Better Extensively illustrated with maps, charts, tables, and over 80 photographs Accompanied by a comprehensive website (www.wiley.com/go/cities) featuring further examples and case studies, discussion and essay questions, chapter outlines and links to useful online resources and films and documentaries "--Provided by publisher.
"A complete introduction to the history, evolution, and future of the modern city, this book covers a wide range of theory, including the significance of space and place, to provide a balanced account of why cities are an essential part of the global human experience"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cities and towns -- Social aspects; Sociology, Urban; Urbanization -- Social aspects